2018
DOI: 10.1002/ijc.31841
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of BRCA1 and BRCA2 pathogenic variants in a large, unselected breast cancer cohort

Abstract: Breast cancer patients with BRCA1/2-driven tumors may benefit from targeted therapy. It is not clear whether current BRCA screening guidelines are effective at identifying these patients. The purpose of our study was to evaluate the prevalence of inherited BRCA1/2 pathogenic variants in a large, clinically representative breast cancer cohort and to estimate the proportion of BRCA1/2 carriers not detected by selectively screening individuals with the highest probability of being carriers according to current cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 38 publications
(90 reference statements)
3
41
0
Order By: Relevance
“…However, it is higher than reported in a large international prospective study of clinically ascertained carriers of a BRCA1 pathogenic variant, with median age at diagnosis of breast and ovarian cancer of 44 and 54 years, respectively [23]. On the other hand, a recent large study on unselected women with breast cancer in Sweden found a mean age at diagnosis of 50.3 years in women with a pathogenic BRCA1 variant [24]. This illustrates that the penetrance of BRCA1 pathogenic variants may differ, depending on the mode of ascertainment.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, it is higher than reported in a large international prospective study of clinically ascertained carriers of a BRCA1 pathogenic variant, with median age at diagnosis of breast and ovarian cancer of 44 and 54 years, respectively [23]. On the other hand, a recent large study on unselected women with breast cancer in Sweden found a mean age at diagnosis of 50.3 years in women with a pathogenic BRCA1 variant [24]. This illustrates that the penetrance of BRCA1 pathogenic variants may differ, depending on the mode of ascertainment.…”
Section: Discussionmentioning
confidence: 69%
“…The PCR products were analysed by agarose gel electrophoresis and Sanger sequencing. The reference sequence NG_005905.2 (NM_007294.3) and traditional numbering of exons [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] was used.…”
Section: Dna and Rna Analysesmentioning
confidence: 99%
“…Most recently, the breast cancer type 1/2 susceptibility protein (BRCA1/2) mutation prevalence in 5122 unselected Swedish breast cancer patients was shown to be <2% [55] and the prevalence of BRCA1/2 and partner and localizer of BRCA2 (PALB2) germline mutations in 2769 unselected breast cancer patients the Chinese population were 2.7% (BRCA1), 2.7% (BRCA2) and 0.9% (PALB2) [56]. The scientific community should be asking how it can be justified that BRCA genetic testing is already demanded by some biotechnology companies?…”
Section: Somatic Mutation Theory (Smt)mentioning
confidence: 99%
“…3,5 Identification of individuals with inherited BRCA1/2 pathogenic variants is beneficial as knowledge of this fundamentally impacts medical management. [6][7][8] Extensive efforts have developed databases with well-documented, annotated and freely accessible BRCA1/2 variant information used as a universal reference for diagnostic, treatment and prevention strategies. These data however have derived predominantly from studies involving populations of European descent.…”
Section: Introductionmentioning
confidence: 99%